2019
DOI: 10.1128/iai.00431-19
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 PromotesBrucella abortusClearance by Controlling Bactericidal Activity of Macrophages and CD8+T Cell Differentiation

Abstract: To date, the implications of interleukin 6 (IL-6) for immune responses in the context of Brucella infection are still unknown. In the present study, we found that Brucella abortus infection induced marked production of IL-6 in mice that was important for sufficient differentiation of CD8+ T cells, a key factor in Brucella clearance. Blocking IL-6 signaling also significantly induced serum IL-4 and IL-10, together with a decreased gamma interferon (IFN-γ) level, suggesting that IL-6 is essential for priming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
(61 reference statements)
2
25
0
Order By: Relevance
“…Furthermore, IL-6 and TNF-α play several functions in the innate and adaptive immunity, with IL-6 being a cytokine participating in B cell growth, CD4 + T cell differentiation and CD8 + T cell cytotoxic functions ( Dienz and Rincon, 2009 ; Lee et al, 2016 ). During infection by B. abortus , IL-6 secretion contributes to host resistance, controlling the bactericidal activity of macrophages ( Hop et al, 2019 ). On the other hand, TNF-α is a pleiotropic cytokine that mediates diverse functions in host-pathogen interactions, playing a role as an autocrine and paracrine factor in macrophages ( Caldwell et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-6 and TNF-α play several functions in the innate and adaptive immunity, with IL-6 being a cytokine participating in B cell growth, CD4 + T cell differentiation and CD8 + T cell cytotoxic functions ( Dienz and Rincon, 2009 ; Lee et al, 2016 ). During infection by B. abortus , IL-6 secretion contributes to host resistance, controlling the bactericidal activity of macrophages ( Hop et al, 2019 ). On the other hand, TNF-α is a pleiotropic cytokine that mediates diverse functions in host-pathogen interactions, playing a role as an autocrine and paracrine factor in macrophages ( Caldwell et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has emerged as a key cytokine during bacterial infections, with complex effects on cells of the immune system and context-dependent proinflammatory described properties [ 1 , 30 ]. Moreover, IL-6 deficiency leads to impaired innate and adaptive immunity to parasitic, viral, and bacterial infections [ 29 , 31 , 32 ]. Corroborating previous studies [ 26 , 33 , 34 ], we showed here that Brucella induces IL-6 secretion, and it was recently shown that patients with brucellosis exhibit higher IL-6 levels compared to control patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data demonstrated that macrophages treated with an anti-IL6 monoclonal antibody displayed enhanced susceptibility to B. abortus infection in macrophages, suggesting that the induction of IL-6 is required for bacterial killing [ 32 ]. Here, we showed that IL-6 is not involved in the control of bacterial replication in macrophages within all analyzed times and infection conditions, indicating that IL-6 is not required for the control of B. abortus replication in IL-6 KO macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity of host against B. abortus is likely to be mediated by complicated balance between Th1 and Th2 related immune responses. A recent study showed that IL-6 contribute to resistance against B. abortus in macrophages and CD8+ T cell differentiation, priming the cellular response during the Brucella infection [33]. In addition, the antibody profile of regimens vaccinated with the live attenuated vaccine strains for brucellosis, S19 and RB51, were reported to be predominantly IgG1 whereas they are known to induce strong cellular immunity [34].…”
Section: Discussionmentioning
confidence: 99%